2009
DOI: 10.1007/s00198-009-0969-z
|View full text |Cite
|
Sign up to set email alerts
|

Iliac bone histomorphometry in children with newly diagnosed inflammatory bowel disease

Abstract: Our results indicate that young patients manifest a mild cortical bone deficit at the iliac crest and slow trabecular bone turnover even at diagnosis, in the setting of IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 33 publications
0
46
0
Order By: Relevance
“…Most previous studies that have evaluated BA of pediatric IBD patients have reported significant delay of BA, with a mean difference of 0.5-1.2 years to CA [6,16,17,[32][33][34]. Two studies on IBD patients found no difference between BA and CA [3,5]. Sylvester et al [31] reported no significant difference between BMD Z scores calculated for BA or height age in a cohort of 76 IBD patients; the difference in the mean of CA and BA was 1 year in 58 CD patients.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Most previous studies that have evaluated BA of pediatric IBD patients have reported significant delay of BA, with a mean difference of 0.5-1.2 years to CA [6,16,17,[32][33][34]. Two studies on IBD patients found no difference between BA and CA [3,5]. Sylvester et al [31] reported no significant difference between BMD Z scores calculated for BA or height age in a cohort of 76 IBD patients; the difference in the mean of CA and BA was 1 year in 58 CD patients.…”
Section: Discussionmentioning
confidence: 94%
“…Kappelman et al [9] discussed their power (1,242 patients with IBD, 737 CD) not to be adequate to detect a significant association owing to the rarity of VFs. Two studies with small numbers of patients found no subclinical VFs by X-ray images [5,12]. Although VFA images are not as accurate for detecting VF as X-ray images [37], they offer a practical and safe tool for screening vertebral deformities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these were not newly diagnosed patients and they had received treatment for IBD at the time of study. A recent study with naive pediatric CD and UC patients found that biochemical markers of both bone formation and resorption were low compared with age-and sex-specific reference ranges (107). Histomorphometric data showed that bone formation activity was low on trabecular bone surfaces.…”
Section: Bone Formation Vs Resorption In Ibd Patientsmentioning
confidence: 97%